Caribbean Spaces : Escapes from Twilight Zone - Boyce Davies, Carole (Book collections on Project MUSE., 2013)
"Both a memoir and a scholarly study, this project explores the multivalent meanings of Caribbean space and community in a cross-cultural and transdisciplinary perspective. Drawing on experiential knowledge and theory, Boyce Davies has crafted this set of reflective essays to illuminate the dynamic and ever-changing complexity of Caribbean culture and to trace its migratory patterns in and between the Americas. In weaving the private spaces of the author's individual story with public spaces of Caribbean culture, Boyce Davies crosses many cultural and disciplinary boundaries. Such movements are necessary to understand the interrelated dynamics of race, gender, and sexuality embedded in Caribbean spaces, and also many Caribbean people's traumatic and transformative stories of displacement, migration, and exile. From there, she dwells on the way her knowledge has informed her political vision as it links to broader, black diaspora matters including the 1960s civil rights movement, the environmental catastrophes of Haiti, the failure of the New Orleans levies, technologies such as the iPhone and GPS, and how all these things are understood and informed by a Caribbean logic. Family narratives, local knowledge, poems, literary analyses, descriptions of artwork, and accounts of spiritual practices are cohesively used to sustain a comprehensive theoretical analysis fostered by the author's extensive fieldwork and research. Ultimately, Boyce Davies reestablishes the link between theory and practice and intellectual work and activism which, the author argues, marked the beginning of Black Studies itself"--